2011
DOI: 10.1016/s0300-9572(11)70147-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and hemodynamic effects of leaning during CPR

Abstract: Background Cardiopulmonary resuscitation (CPR) guidelines recommend complete release between chest compressions (CC). Objective Evaluate the hemodynamic effects of leaning (incomplete chest wall release) during CPR and the prevalence of leaning during CPR. Results In piglet ventricular fibrillation cardiac arrests, 10% and 20% (1.8 kg and 3.6 kg, respectively), leaning during CPR increased right atrial pressures, decreased coronary perfusion pressures, and decreased cardiac index and left ventricular myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…46 Although data are sparse regarding outcomes related to leaning, animal studies have shown that leaning increases right atrial pressure and decreases cerebral and coronary perfusion pressure, cardiac index, and left ventricular myocardial flow. [46][47][48] Human studies show that a majority of rescuers often lean during CPR and do not allow the chest to recoil fully. 49,50 Therefore, the expert panel agrees that leaning should be minimized.…”
Section: Full Chest Recoil: No Residual Leaningmentioning
confidence: 99%
“…46 Although data are sparse regarding outcomes related to leaning, animal studies have shown that leaning increases right atrial pressure and decreases cerebral and coronary perfusion pressure, cardiac index, and left ventricular myocardial flow. [46][47][48] Human studies show that a majority of rescuers often lean during CPR and do not allow the chest to recoil fully. 49,50 Therefore, the expert panel agrees that leaning should be minimized.…”
Section: Full Chest Recoil: No Residual Leaningmentioning
confidence: 99%
“…For adult patients, leaning is conventionally defined as > 2.5 kg of residual force [4], but the impact of sternal force on hemodynamics is continuous, no safe limit has been documented, and optimal treatment of intermediate levels of residual force is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CPR monitors provide feedback on rate, depth and release force (RF) of chest compressions. Excessive RF ("leaning") is common in practice and impedes chest wall recoil, venous return, and blood flow [4]. Leaning can be reduced with real-time feedback [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…'Residual leaning' on the chest after each compression by the rescuer impairs the coronary perfusion pressures and cardiac index, which are crucial for myocardial and systemic perfusion, respectively, (17) during CPR. ACLS crew performing manual CPR must pay special attention to ensure complete chest recoil between compressions.…”
Section: Chest Recoilmentioning
confidence: 99%